2019
DOI: 10.31254/phyto.2019.8501
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical and Neurotoxicity Evaluation of Methanolic Leaf-Extract of Moringa oleifera

Abstract: Objective: As a plant with a host of medicinal properties used for treating various ailments, the research set out to investigate the neurotoxic effect of methanol leaf-extract of Moringa oleifera, as well as explore its phytochemical constituents. The amphiphylic property of methanol as a solvent was exploited to extract non-polar and medium polar phytoconstituents. Methods: Forty (40) male Swiss white mice were randomly grouped into four (n=10 per group). The control animals receive normal saline (p.o.) whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…In the present study, only LD50 of aqueous root extract of M. oleifera was determined, and the result was suggestive of a high toxicity at 1264.91 mg/kg b.w. Previously, Bisong et al (2019) and Kadam and Gaykar (2017) reported the LD50s of methanol-and -diethyl-ether root extracts of M. oleifera to be greater than 5000 mg/kg and 2000 mg/kg, respectively.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In the present study, only LD50 of aqueous root extract of M. oleifera was determined, and the result was suggestive of a high toxicity at 1264.91 mg/kg b.w. Previously, Bisong et al (2019) and Kadam and Gaykar (2017) reported the LD50s of methanol-and -diethyl-ether root extracts of M. oleifera to be greater than 5000 mg/kg and 2000 mg/kg, respectively.…”
Section: Discussionmentioning
confidence: 95%
“…Potassium, calcium, phosphorus, iron, vitamins A and D, vital amino acids, antioxidants including beta-carotene, vitamin C, and flavonoids have all been shown to be abundant in this plant's leaves (Abd-alwahab, 2018). Alkaloids, tannins, phenolics, saponins, and steroids are additional antinutrients that were found (Bisong et al, 2019). Zeatin, quercetin, β-sitosterol, caffeoylquinic acid, and kaempferol are abundantly and commonly found in the Moringa plant (Milla et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, only LD50 of aqueous root extract of M. oleifera was determined, and the result was suggestive of a high toxicity at 1264.91 mg/kg b.w. Previously, Bisong et al (2019) and Kadam and Gaykar (2017) reported the LD50s of methanol-and -diethyl-ether root extracts of M. oleifera to be greater than 5000 mg/kg and 2000 mg/kg, respectively.…”
Section: Discussionmentioning
confidence: 95%
“…Potassium, calcium, phosphorus, iron, vitamins A and D, vital amino acids, antioxidants including beta-carotene, vitamin C, and flavonoids have all been shown to be abundant in this plant's leaves (Abd-alwahab, 2018). Alkaloids, tannins, phenolics, saponins, and steroids are additional antinutrients that were found (Bisong et al, 2019). Zeatin, quercetin, β-sitosterol, caffeoylquinic acid, and kaempferol are abundantly and commonly found in the Moringa plant (Milla et al, 2021).…”
Section: Introductionmentioning
confidence: 94%